PELATIHAN PENGELOLAAN SAMPAH DI SEKOLAH DALAM MENUJU INDONESIA SADAR SAMPAH - Annur, Shohifah; Dewi, Lina Marliana (Jurnal Berdaya Mandiri, 2023)
The purpose of this community service to improve the awareness about the waste to the junior and senior high school students. The target of this program is to change the policy of waste management in the school. This activities was begin by locating KKM (Community Service Program) students from the university to the schools around the KKM locations. These KKM students was placed as a field assistants in the school waste management. The next step, we developed several workshop about waste management in the school. The targets of this program are teachers, students and gardeners in the school. The implementation of this new waste management will be monitored and evaluated by lecturers and the KKM students. This program has been implemented in three schools, SMPN 1 Mancak, Serang, SMA Al Irsyad Waringinkurung, and SMA 1 Baros. Keywords: waste, management, school, KKM